Evaluating a targeted person-centred pain management intervention programme in lumbar spine surgery - a controlled segment-specific before-and-after interventional design - Eva Angelini; Axel Wolf; Helle Wijk; Helena Brisby; Adad Baranto (BMC, 2024)
Abstract Background Postoperative pain management in lumbar spine surgery care remains a challenge. The aim of this study was to evaluate the impact of a person-centred postoperative pain management intervention programme on lumbar spine surgery patients on postoperative pain, shared decision-making, and satisfaction with postoperative pain management. Methods The study was performed with a controlled before-and-after interventional design in an orthopaedic unit at a university hospital. Person-centred pain management for patients undergoing spine surgery was developed in co-creation by a multi-professional team and implemented throughout the care pathway. The usual care group (pre-intervention) served as a comparison to the intervention group. Pain intensity, shared decision-making in pain management, and patient satisfaction with results of pain management, served as patient-reported measures, collected using the International Pain Outcomes questionnaire and analysed using descriptive statistics. Results The intervention showed no benefit for patients' pain and satisfaction, while shared decision-making in pain management was significant lower in the intervention group than in the conventional group. The per-protocol analysis showed no significant differences between groups. Conclusion The initial assumption of the study, that the implementation of a co-created structured person-centred care pathway would improve patient-reported outcomes, was not confirmed. The periodically low fidelity to the intervention due to organizational constraints (due to sub-optimal organizational conditions and managerial support) may have affected the results.